Impact of Indian Mustard (Brassica juncea) and Flax (Linum usitatissimum) Seed Meal Applications on Soil Carbon, Nitrogen, and Microbial Dynamics - Autumn S. Wang; Ping Hu; Emily B. Hollister; Katie L. Rothlisberger; Anil Somenahally; Tony L. Provin; Frank M. Hons; Terry J. Gentry (Applied and Environmental Soil Science)
There is a critical need to investigate how land application of dedicated biofuel oilseed meals affects soil ecosystems. In this study, mustard (Brassica juncea) and flax (Linum usitatissimum) seed meals and sorghum-sudangrass (Sorghum bicolor) were added to soil at levels of 0, 1, 2.5, and 5% (w/w). Both the type of amendment and application rate affected soil organic C, total C & N, and C & N mineralization. Mustard meal amendment initially inhibited C mineralization as compared to flax, but >50% of mustard and flax organic C was mineralized within 51 d. Nitrogen mineralization was similar for flax and mustard, except for the 2.5% rate for which a lower proportion of mustard N was converted to nitrate. The mustard meal greatly impacted microbial community composition, appearing to select for specific fungal populations. The potential varying impacts of different oilseed meals on soil ecosystems should be considered when developing recommendations for land application.